Analysis of English Listening Materials and the Compatibility to Curriculum - Zulfah Fakhruddin; Arqam Arqam; Irma Maming (JELITA, 2024)
This study aims to describe English listening materials taught by teachers in EFL class and the compatibility between available English listening materials teachers use and curriculum. It is due to teaching listening requires the use of media such as video, compact disk, and computer. The use of those media demands teachers’ competence in operating them. This study uses descriptive qualitative method. The subject of the research is thirteen English teachers. Research data was collected by using documentation and interview. The data was analyzed by using qualitative procedure which includes transcription, coding, categorizing, and conluding. The findings showed that English listening materials in EFL classroom are categorized into three. They are media, content, and exercise. English listening materials are in line to English curriculum. Teachers use materials and methods that are suitable to learning outcome of English listening skills.